An outbreak of methicillin resistant Staphylococcus aureus infection in a rugby football team. Issue 2 (June 1998) - Stacey, A R; Endersby, K E; Chan, P C; Marples, R R
Abstract : Outbreaks of infection caused by methicillin resistant Staphylococcus aureus are common in hospitals and nursing homes, but until now none have been reported in the community. This is a report of an outbreak involving five members of a rugby football team.